The Economics Of Higher Education Investment And Graduate Earnings: The Mediating Effect Of Skill Acquisition - Benlaria Houcine (جامعة الوادي University of Eloued, 2024)
This investigation looks into how gaining skills links higher education investments to future earnings for postgraduate individuals in Saudi Arabia. Analyzing the mechanisms through which educational investments yield economic returns is imperative for synchronizing educational methodologies with labour market requirements, particularly as Saudi Arabia transitions toward a knowledge-oriented economy. This inquiry aims to delineate the determinants of graduate earnings and elucidate the manner in which skill acquisition enhances employability and the potential for increased income. For this investigation, a meticulously structured survey was administered to a cohort of 176 recent graduates from Al-Jouf, Hail, and Northern Border Universities. The survey scrutinized the influences of tuition fees, governmental subsidies, parental financial assistance, scholarships, and vocational training initiatives on the processes of skill acquisition and the resultant earnings of graduates. The research utilized Structural Equation Modeling (SEM) to explore how higher education investments correlate with skill improvement and economic achievements. The SEM framework assessed both direct and indirect effects, thereby underscoring the role of skill acquisition as a crucial mediating factor in the relationship between educational investment and earnings. A positive correlation exists between educational investments and graduate earnings, mainly when skill acquisition is considered. Programs focused on practical, technical, and soft skills have been shown to enhance employability and income levels. These findings underscore the necessity for educational reforms emphasizing skill development, aligning with the demands of the Saudi labour market by Vision 2030
Keywords: Higher Education; Investment; Graduate Earnings; Skill Acquisition; Labor Market; Economic Outcomes; Vision 2030; Saudi Arabia